Marianne A.

asked • 08/25/15

Can anyone help me with this? I'm suppose to use resolution to prove that [(p ? q) ^ (q ? (r ^ s))] ? (p ? s)

I have to use resolution to prove these inferences are valid [(p → q) ^ (q → (r ^ s))] → (p → s) ?

1 Expert Answer


Still looking for help? Get the right answer, fast.

Ask a question for free

Get a free answer to a quick problem.
Most questions answered within 4 hours.


Find an Online Tutor Now

Choose an expert and meet online. No packages or subscriptions, pay only for the time you need.